Processos comunicacionais em curadoria e produção do conhecimento: a trajetória de criação do projeto Genocídio Armênio nos domínios da arte contemporânea e da memória - Demercian, Roseli Conceição de Moraes Rojas (2017)
Art in postmodernity does not survive by itself, without generating influxes in the social environment. It must make explicit the worldviews that structure reality, developing a multifaceted activity. As the art system expands throughout the world, so does the demand for curators who see a remarkable strengthening of their role. Thus, we discuss in the present thesis what should be expected of the art curator to develop criteria in the construction of an exhibition, with a new narrative communicational, raising the following hypotheses: what is the practical dimension of curatorial action and its characteristics current? Is it the art curator's job to educate the target audience? The general objective, therefore, is the study of how the curator's action should be, based on a legitimizing knowledge of contemporaneity; and its specific objective is the development of general criteria and models for this practical action, indent to utopias, in a method embodied in the space / time / occupation triad. The curator is an actor whose functions, methodology and activity have not yet been sufficiently explored in scientific research, which in practice have been diffused, marked by a strong empiricism that does nothing to develop curative theories. He must propose, through mediation, not only the orientation of the artist, but also the education of the gaze, thus revealing an effective interpretation of the world. The curatorship that served as a basis for this thesis was structured in four ethnographic concepts, namely: genocide of the Armenian people, memory, lectures and affective cartography. They were theorists: HANS ULBRICH OBRIST, who motivated the investigation of the materialization of the exhibition space, starting from conversations, meetings and exchanges, with the reinvention of a new meeting point with art, establishing relational and communicational criteria; JOHN DEWEY, whose concepts propitiated a new vision of research resulting from the junction between the new and the old, through the experience of the real, in which the impulsion gains form and solidity; and LÚCIA LEÃO, whose teachings raised the need to understand the process of creative construction of experience, resulting from a mapping of the global and panoramic view of the terrain on which the labyrinth would be projected. As a historical fact, the genocide of the Armenian people, recalled in its 100 years, the methodology used was eminently empirical based on reports, interviews and recordings, collecting files, documents of affection and memories. In order to achieve its purpose, it had, necessarily, an interdisciplinary character, involving, therefore, different areas of knowledge. The field survey lasted for approximately twelve months and its execution lasted for the same period. It is believed that the relevance of this research rests on its provocative character of affections because it revisits the memory and, at the same time, invites the dialogue. This aetiological construction requires study and repertoire acquisition, so that, based on these hypotheses, a great number of aesthetic, historical, political and social relations can be established. It has been demonstrated in this way that the final destination of the archive lies not in its own narrative but in the history that it makes possible